2015
DOI: 10.1007/s12161-015-0156-0
|View full text |Cite
|
Sign up to set email alerts
|

PCR-Based Detection and Quantification of a Transgenic Glyphosate-Tolerant Canola Using a Novel Reference Gene System

Abstract: Development and commercialization of a transgenic crop depends upon the availability of a reliable quantitative assay sensitive enough to detect low level presence of transgenic material in mixed seed or in a commercial product. An appropriate species-specific endogenous control also is necessary for accurate quantification. A novel mode of transgenic tolerance to glyphosate, whereupon an engineered acetylase detoxifies glyphosate, was recently developed and incorporated into transgenic canola (Brassica napus)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 13 publications
2
8
0
Order By: Relevance
“…Thus, FatA(A) primer/probe DNA sequences seem to be suitable for absolute quantification of GE canola events by ddPCR. Our observation confirms the work of Henderson et al [ 9 ] who reported FatA(A) to be a suitable reference gene for real-time quantitative PCR analysis of GE canola events. An example of ddPCR amplitude plot for CruA and FatA(A) endogenous reference genes is provided in Fig.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Thus, FatA(A) primer/probe DNA sequences seem to be suitable for absolute quantification of GE canola events by ddPCR. Our observation confirms the work of Henderson et al [ 9 ] who reported FatA(A) to be a suitable reference gene for real-time quantitative PCR analysis of GE canola events. An example of ddPCR amplitude plot for CruA and FatA(A) endogenous reference genes is provided in Fig.…”
Section: Resultssupporting
confidence: 92%
“…Based on 1.129 and 1.235 pg weight per haploid genome, and if 100 ng canola genomic DNA is used for PCR, there will be approximately 80,000–88,000 haploid genomic DNA copies. The use of 100 ng genomic DNA for PCR has also been reported to correspond to approximately 87,000 haploid copies of the B. napus genome [ 9 ]. For Legend and Eagle non-GM canola DNA, the number of copies for HMG-I/Y and FatA(A) varied from 6000 to 7000 for 10 ng DNA ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This accounts for a greater difference between the ratios rather than the absolute values. FatA(A) was developed to be specific for the A sub-genome of all three canola species B. napus (A and C sub-genomes), B. rapa (A sub-genome) and B. juncea (A and B sub-genomes) ( Henderson, Harmon, & Zhong, 2016 ). When tested on 6 different Brassica species which contain the A, B and C sub-genomes ( B. napus , B. rapa , B. juncea , B. nigra - B sub-genome, B. carinata - B and C sub-genomes, and B. oleracea - C sub-genome), all assays except for FatA(A) showed amplification in all species.…”
Section: Resultsmentioning
confidence: 99%
“…All the other assays showed amplification with all the species tested, with the λ values reported in Table S3 (Supplementary Information). Thus, the assay for FatA(A) showed amplification results only with the three canola species B. rapa , B. napus and B. juncea , for which the assay was specifically designed ( Henderson et al, 2016 ). Even though FatA(A) measurements are not able to distinguish which of the above mentioned species is present, they can detect canola species in single copy and discriminate against impurities.…”
Section: Resultsmentioning
confidence: 99%